+0  
 
0
170
1
avatar

Let $f(x)=7x+5$ and $g(x)=x-1$. If $h(x)=f(g(x))$, then what is the inverse of $h(x)$?

Guest Mar 18, 2018

Best Answer 

 #1
avatar+7324 
+2

f(x)  =  7x + 5

g(x)  =  x - 1

 

h(x)  =  f( g(x) )  =  f( x - 1 )  =  7(x - 1) + 5  =  7x - 7 + 5  =  7x - 2

 

h(x)  =  7x - 2

                            To find the inverse, let's replace  h(x)  with  y .

y  =  7x - 2

                            Solve for  x  ....add  2  to both sides of the equation.

y + 2  =  7x

                            Divide both sides by  7 .

(y + 2)/7  =  x

 

x  =  (y + 2)/7      So the inverse of  h(x)  is..

 

h-1(x)  =  (x + 2)/7

hectictar  Mar 19, 2018
 #1
avatar+7324 
+2
Best Answer

f(x)  =  7x + 5

g(x)  =  x - 1

 

h(x)  =  f( g(x) )  =  f( x - 1 )  =  7(x - 1) + 5  =  7x - 7 + 5  =  7x - 2

 

h(x)  =  7x - 2

                            To find the inverse, let's replace  h(x)  with  y .

y  =  7x - 2

                            Solve for  x  ....add  2  to both sides of the equation.

y + 2  =  7x

                            Divide both sides by  7 .

(y + 2)/7  =  x

 

x  =  (y + 2)/7      So the inverse of  h(x)  is..

 

h-1(x)  =  (x + 2)/7

hectictar  Mar 19, 2018

41 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.